Improving Constructing Child Friendly School Culture Through Symbolic Interaction - Fritz Hotman Syahmahita Damanik; Oman Sukmana; Tri Sulistyaningsih (Journal of Education and Teaching Learning, 2026)
School culture is not a static institutional given but a dynamic social achievement produced and reproduced through the everyday interpretive interactions of all stakeholders: teachers, students, parents, and administrators. This article investigates how the concept of "child-friendly culture" is socially constructed, negotiated, and internalized as a living school culture within Indonesian Child-Friendly Schools (Sekolah Ramah Anak/SRA). Drawing on a qualitative case study conducted at SMA Swasta Harapan Mandiri Medan, an officially SRA, designated school in a multicultural urban context, the article applies the theoretical framework of Constructivist Symbolic Interactionism as elaborated by Herbert Blumer (1969), Kathy Charmaz (2014), and Norman K. Denzin (2019). This integrated framework attends to three dimensions of meaning-making: the symbolic interactions through which "child-friendly" meanings are communicated and shared; the constructivist processes through which these meanings are shaped by actors' reflexive engagement with their social contexts and lived experiences; and the interpretive flexibility through which different stakeholder groups construct divergent yet interrelated understandings of what child-friendly school culture means in practice. Data collected through in-depth interviews, participant observation of school cultural routines, and documentary analysis reveal that "child-friendly culture" is most authentically enacted not through formal policy compliance but through the accumulated symbolic practices of daily school life. The article argues that school culture literacy, the capacity of educational actors to reflectively understand, critically evaluate, and actively shape the symbolic environment of their school, is a precondition for genuine SRA implementation.